Benzene-1,3-diol-1,4-diazabicyclo[2.2.2]octane (1/1) - Arman, H.D.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
There are two independent but virtually identical molecules of each component in the asymmetric unit of the title 1:1 adduct, C(6)H(12)N(2)center dot C(6)H(6)O(2). In the crystal, the constituents are connected into a supramolecular chain along the b axis by O-H...N hydrogen bonds. Weak C-H...O bonds cross-link the chains.